FUNGSI TUTURAN TOKOH PADA WACANA WAYANGMBELING "REKAYASA WIBISANA" KARYA KI MAKSUM SUKACARITA - A, Riniwati S (Majalah Transformatika, 2010)
Man as a social creature needs other to express how he feels and thinks. The clearer the he thinks the clearer he is understood by others. He has special purposes when he speaks. The functions  of  speech  involves  (1) expressions, (2) information,  (3)  exploration,  (4) persuasion, and (5) entertainment. Keywords : the function of language, speech function, relevant in life.